2018
DOI: 10.9775/kvfd.2017.19081
|View full text |Cite
|
Sign up to set email alerts
|

Çiğ Süt ve Süt Ürünlerinde Listeria monocytogenes Varlığı ve Antibiyotik Direnci

Abstract: How to Cite This ArticleAksoy A, Sezer Ç, Vatansever L, Gülbaz G: Presence and antibiotic resistance of Listeria monocytogenes in raw milk and dairy products . Kafkas Univ Vet Fak Derg, 24 (3): 415-421, 2018. AbstractIn this study, the presence of Listeria monocytogenes in raw milk and milk products produced from raw milk by traditional method, such as cheese and butter using cultural and molecular techniques and the antibiotic resistances were investigated. Isolation was performed using the FDA technique. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Resistance to TRS has also been seen in other studies [26,106]. Since this antibiotic is used in listeriosis treatment, the finding of TRS resistance in food chain isolates is concerning [107][108][109]. An earlier study from France reported an overall high rate of susceptibility of clinical L. monocytogenes strains to a range of antibiotics, including those used in listeriosis treatment [31].…”
Section: Antimicrobial Resistance Of L Monocytogenes Isolatesmentioning
confidence: 79%
“…Resistance to TRS has also been seen in other studies [26,106]. Since this antibiotic is used in listeriosis treatment, the finding of TRS resistance in food chain isolates is concerning [107][108][109]. An earlier study from France reported an overall high rate of susceptibility of clinical L. monocytogenes strains to a range of antibiotics, including those used in listeriosis treatment [31].…”
Section: Antimicrobial Resistance Of L Monocytogenes Isolatesmentioning
confidence: 79%
“…Today, antibiotic resistance is a wide spreading issue addressed by the World Health Organization (WHO). Aksoy et al (1) stated that they found intermediate and resistant to amikacin, meropenem, vancomycin and penicillin G, and Trimethoprim-Sulfamethoxazole in 15 L. monocytogenes isolates they isolated from raw cow milk, cheese and butter. Jamali and Redmehr (23) stated resistance against penicillin G, amoxicillin-clavulanic acid, chloramphenicol, erythromycin, and tetracycline at the rates of 66.7%, 23.8%, 19%, 4.8% and 52.4%, respectively, in 17 L. monocytogenes isolates they have isolated from the clinical mastitis infections of cows.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, the inhibition zones were measured on Mueller-Hingon F agar plates and evaluated as resistant (R), intermediate (I) and susceptible (S) based on the breakpoints suggested by EUCAST (18) for L. monocytogenes on ampicillin, penicillin G, oxacillin, erythromycin, trimethoprim-sulfamethoxazole, meropenem and for the other antibiotic discs commented based on the breakpoints suggested by CLSI ( 14) for other Gram-positive bacteria (1,13,14,18). Escherichia coli (ATCC ® 25922™) were used as reference on antibitoic susceptability tests.…”
Section: Investigation Of Antibiotic Susceptibility Of Isolated Listeria Isolatesmentioning
confidence: 99%